Misfolding and aggregation of protein in progressive neurodegenerative diseases: novel biomarkers and intervention strategies - Wang, Zhichao (Edelweiss Applied Science and Technology, 2026)
This review aims to examine the role of protein misfolding and aggregation in the pathogenesis of neurodegenerative diseases (NDDs) and to evaluate emerging biomarkers and therapeutic strategies. A comprehensive literature-based approach was adopted to synthesize recent advances in molecular mechanisms, diagnostic tools, and intervention methods related to major NDDs, including Alzheimer’s, Parkinson’s, and Huntington’s diseases. The findings indicate that protein misfolding leads to the formation of toxic aggregates that disrupt neuronal function and drive disease progression. While traditional biomarkers such as amyloid-beta and alpha-synuclein remain important, they are limited in detecting early-stage disease; in contrast, emerging biomarkers, including tau oligomers and blood-based indicators, demonstrate improved sensitivity for preclinical diagnosis. Regarding treatment, approaches such as immunotherapy, molecular chaperones, aggregation inhibitors, and gene-based therapies show promising potential, although challenges related to delivery, specificity, and long-term safety persist. Overall, advances in biomarker development and targeted therapies offer new opportunities for early diagnosis and disease modification. Continued optimization may enhance diagnostic accuracy, enable timely intervention, and support personalized treatment strategies for patients with NDDs.